THERMOCHEMISTRY OF SILICATE SOLID-SOLUTIONS - Newton, R; Wood, B; Kleppa, O (1981)
Brief reviews are given of relations on the three clinopyroxene joins of diopside with jadeite, Ca Tschermak's molecule, and clinoenstatite; HF solution data for the alkali feldspars, plagioclase, olivine, and melilite; and the grossular-pyrope join.-R.A.H.